Medical cannabis or cannabinoids for chronic pain: a clinical practice guideline. (8th September 2021) - Busse, Jason W; Vankrunkelsven, Patrick; Zeng, Linan; Heen, Anja Fog; Merglen, Arnaud; Campbell, Fiona; Granan, Lars-Petter; Aertgeerts, Bert; Buchbinder, Rachelle; Coen, Matteo; Juurlink, David; Samer, Caroline; et al.
Abstract: Clinical question: What is the role of medical cannabis or cannabinoids for people living with chronic pain due to cancer or non-cancer causes? Current practice: Chronic pain is common and distressing and associated with considerable socioeconomic burden globally. Medical cannabis is increasingly used to manage chronic pain, particularly in jurisdictions that have enacted policies to reduce use of opioids; however, existing guideline recommendations are inconsistent, and cannabis remains illegal for therapeutic use in many countries. Recommendation: The guideline expert panel issued a weak recommendation to offer a trial of non-inhaled medical cannabis or cannabinoids, in addition to standard care and management (if not sufficient), for people living with chronic cancer or non-cancer pain. How this guideline was created: An international guideline development panel including patients, clinicians with content expertise, and methodologists produced this recommendation in adherence with standards for trustworthy guidelines using the GRADE approach. The MAGIC Evidence Ecosystem Foundation (MAGIC) provided methodological support. The panel applied an individual patient perspective. The evidence: This recommendation is informed by a linked series of four systematic reviews summarising the current body of evidence for benefits and harms, as well as patient values and preferences, regarding medical cannabis or cannabinoids for chronic pain. Understanding the recommendation: The recommendation is weak because of the close balance between benefits and harms of medical cannabis for chronic pain. It reflects a high value placed on small to very small improvements in self reported pain intensity, physical functioning, and sleep quality, and willingness to accept a small to modest risk of mostly self limited and transient harms. Shared decision making is required to ensure patients make choices that reflect their values and personal context. Further research is warranted and may alter this recommendation.